2014 IEEE International Symposium on Information Theory 2014
DOI: 10.1109/isit.2014.6874897
|View full text |Cite
|
Sign up to set email alerts
|

Optimal simultaneous detection and signal and noise power estimation

Abstract: Abstract-Simultaneous detection and estimation is important in many engineering applications. In particular, there are many applications where it is important to perform signal detection and Signal-to-Noise-Ratio (SNR) estimation jointly. Application of existing frameworks in the literature that handle simultaneous detection and estimation is not straightforward for this class of application. This paper therefore aims at bridging the gap between an existing framework, specifically the work by Middleton et al.,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The procedure is stopped for the first time when Gm 0 ,m 1 = Rm 0 ,m 1 . The min term in (20) signifies the detection cost if the decision rule (17) is employed, while the last two terms correspond to the estimation cost, i.e., the deviation of the estimatorθ * from the true SNR. At first glance, the optimal decision rule as well as the optimal estimator seem equivalent to Bayesian solutions because of the following reason: The term E can be interpreted as the conditional moments of the posterior distribution of ρ (or, θ) with prior µ, and the optimal estimatorθ * as the posterior expected value of θ − 2.…”
Section: Joint Detection and Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure is stopped for the first time when Gm 0 ,m 1 = Rm 0 ,m 1 . The min term in (20) signifies the detection cost if the decision rule (17) is employed, while the last two terms correspond to the estimation cost, i.e., the deviation of the estimatorθ * from the true SNR. At first glance, the optimal decision rule as well as the optimal estimator seem equivalent to Bayesian solutions because of the following reason: The term E can be interpreted as the conditional moments of the posterior distribution of ρ (or, θ) with prior µ, and the optimal estimatorθ * as the posterior expected value of θ − 2.…”
Section: Joint Detection and Estimationmentioning
confidence: 99%
“…In [19], it was shown that a scheduling scheme performed detection in an energy-efficient manner by jointly estimating the SNR. However, [20] reported that the techniques developed in some of the papers mentioned above were not readily applicable to the problem of joint detection and signal and noise power estimation. For a Bayesian formulation, it was shown [20, Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation